Utjecaj telekomunikacija na uključivanje jadranskog područja u europske turisticke prometne tijekove - Burmaz, Branimir; Tudor, Branko; Matešić, Ante (Promet - Traffic&Transportation, 2012)
The paper deals with the interdependent aspect of telecommunications and tourist trade, their correlation and common interests. Contribution of telecommunications is manifested in quality, structuring and materialization of business policy of the travel trade. As different, by the action of demographic, economic, technological and social/cultural forces it tends to bring together the tourist trade essentially affects the functioning and development of telecommunications as one of its infrastructure elements or, otherwise, a specific segment. Travel market being directly integrated into the international market most quickly reacts to the international development trends, the rejvre to the development of telecommunications as well. The indispensable introduction of new services is further pronounced in the changes to be caused by the integration of the 12 national markets of the EC in to a single unified market with access granted only upon eliminating all technical obstacles for the appearance on this market.